On Fluctuations of a Nonmonotone Marked Point Process - Dshalalow, J.H.; Robinson, R. (Інститут проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
The present article investigates a bivariate recurrent process, which can describe the behavior of a nonmonotone financial instrument observed at random times. We are able to find explicitly the joint distribution of the highest value of the instrument prior to its first drop using a game-theoretic approach.